(untitled) (Proceedings of the International Conference on Future of Education, 2021)
: Developing modern technologies in the education sector requires brand new decisions to improve the proceeding and memorise information. The accelerated study rate reduces the amount of concentration and accessible time, so an average student experiences difficulty gathering knowledge and required skills. When placed in such conditions, students and teachers find extraordinary methods for lessons and exercises to simplify acquiring knowledge and fulfilling all the tasks. The Context Board represents the specified topics and provides the ability to disclose a sufficient level of knowledge appropriately. The mentioned draft is based on different ways of memorising and popular technical capacity. The main purpose of this study is to determine the optimal method of the material presentation within the framework of the developed project. The experiments have shown the overall effectiveness of the context boards. The method itself takes into consideration the features of persons with different types of information perception. It is also essential that organising the specified and requested topics allows to systematise information and realise all the significant connections between different subjects and choose the study format.